2014
DOI: 10.1086/677283
|View full text |Cite
|
Sign up to set email alerts
|

Haplodiploidy and the Evolution of Eusociality: Worker Revolution

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Online enhancements: appendixes.abstract: Hamilton suggested that inflated relatedness between sisters promotes the evolution of eusociality in haplodiploid populations. Trive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
(72 reference statements)
0
11
0
Order By: Relevance
“…The theoretical grounds are that when both sexes are properly accounted for in the inclusive fitness calculations, haplodiploidy requires female-biased sex ratios to favour eusociality8. However, recent models suggest that the conditions (polyandry, see above) which favour such biased sex ratios are unlikely to have been present in the early evolution of eusociality254546. Here we have shown that, depending on the type of bivoltine life cycle, haplodiploidy can both inhibit and promote the evolution of reproductive altruism.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The theoretical grounds are that when both sexes are properly accounted for in the inclusive fitness calculations, haplodiploidy requires female-biased sex ratios to favour eusociality8. However, recent models suggest that the conditions (polyandry, see above) which favour such biased sex ratios are unlikely to have been present in the early evolution of eusociality254546. Here we have shown that, depending on the type of bivoltine life cycle, haplodiploidy can both inhibit and promote the evolution of reproductive altruism.…”
Section: Discussionmentioning
confidence: 71%
“…The favourable effects that lifetime monogamy has on the evolution of reproductive altruism and cooperative breeding have both considerable theoretical20254546 and empirical support. Strict parental monogamy has now been well documented as the ancestral state across lineages of the social Hymenoptera and termites with permanent worker castes4748, but the mechanisms are very different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The early stages in the evolution of life required cooperation between simple replicators, which may also have been favoured due to population structure keeping relatives together 131,132 . In contrast, while the possible role of haplodiploid genetics has attracted much attention, both theory and empirical data have led to many concluding that it was a red herring [133][134][135][136][137][138][139] .…”
Section: Indirect Benefits Play the Major Role In Explaining Cooperation Within Speciesmentioning
confidence: 99%
“…Hamilton, 1964;Lehmann et al, 2008;Boomsma, 2009), bivoltinism and asymetrical sex-ratio (e.g. Trivers and Hare, 1976;Seger, 1983;Alpedrinha et al, 2014;González-Forero, 2015;Quiñones and Pen, 2017), coercion (i.e. policing, Wenseleers et al, 2004;Dobata, 2012), queen longevity and competition between queens (e.g.…”
Section: Introductionmentioning
confidence: 99%